Validated Reversed-Phase Ion-Interaction High-Performance Liquid Chromatography for Quantitation of Nitrate Content of Clausena anisata (Willd.) Hook. f. ex Benth. Leaves. (14th March 2020) - Monton, Chaowalit; Suksaeree, Jirapornchai; Luprasong, Chitradee
Abstract : This work sought to validate the reversed-phase ion-interaction high-performance liquid chromatography for quantifying the nitrate content in the extract and raw material of Clausena anisata (Willd.) Hook. f. ex Benth. leaves. Three extraction methods (i.e., decoction, infusion, and ultrasound-assisted extraction) were investigated and compared. Furthermore, the effect of the solid-to-solvent ratio and defatting was also evaluated. The validation result showed that the high-performance liquid chromatographic method had a linear response ( R 2 = 0.9999) in the range of 1–50 μ g/mL. The limit of detection and limit of quantitation were 0.25 μ g/mL and 0.75 μ g/mL, respectively. In addition, the method was specific, precise, and accurate. So the validated method was suitable for determination of the nitrate content in C. anisata leaves. Infusion of a nondefatted sample using a solid-to-solvent ratio of 1 : 10 gave the highest nitrate content in the raw material, 0.251 ± 0.003%. In case of a defatted sample, decoction provided the highest nitrate content, 0.309 ± 0.001%. Increasing the solid-to-solvent ratio and defatting had a huge effect on the nitrate content of C. anisata leaves extracted from decoction. To the best of our knowledge, this is the first report that used the reversed-phase ion-interaction high-performance liquid chromatography for quantifying the nitrate content in C. anisata leaves. Furthermore, the authors suggested that nitrate could be used as a standard marker for quality control of C. anisata leaves' extract and raw material.